Quararibea latifolia (Malvaceae), a new and possibly extinct species from the Atlantic Forest of Minas Gerais, Brazil - Ferreira, Carlos D. M.; Alverson, William S.; Bovini, Massimo G. (Phytotaxa, 2026)
During our recent taxonomic revision of Quararibea in Brazil, we encountered a new species from the Atlantic Forest of Minas Gerais, Brazil. We here describe and illustrate Quararibea latifolia, which is morphologically similar to Q. bovinii and Q. bragae due to the fasciculate trichomes on its branches and petioles, but differing by its domatia morphology, petiole length, leaf width, and the indumentum of its calyx, petals, and staminal column. This new species is known only from a single collection made in 1944 and our recent efforts to relocate living populations were unsuccessful. As it has not been recorded in over 80 years, we assess it as Critically Endangered (Possibly Extinct). We provide a morphological description, taxonomic comments, photographs, a distribution map, an assessment of its conservation status, and a table comparing the new species morphology to relevant congeners.